The further rise of the career politician. Issue 4 (3rd December 2018) - Henn, Soeren
Abstract Political careers have changed dramatically in the last 50 years. Still, political science research has yet to fully quantify this development. Building on existing literature on career politicians, this study uses a handful of indicators introduced by King (Br J Polit Sci 11(3):249–285, 1981), a new variable (pre-parliamentary occupations), and an original data set compiled by the author. The paper's contribution to the literature is threefold. Firstly, using the variables introduced by King, it observes that a plateau in the number of career politicians has been reached. Secondly, when looking at the occupational background of politicians, the data show a further rise in career politicians. Thirdly, this development is especially prevalent among cabinet ministers.